The Imagery Found in the Client - Umar Umar (LPPM Universitas Terbuka, 2021)
The aim of the reseach is to elaborate the use of the imagery in the novel: The Client. Starting from the definition of Imagery, the imagery found in the novel, then to find out what John Grisham’s - as the writer of the novel - intention to use imagery in his novel. The objectives of analysis is to have some knowledge deeper about the use of imagery in The Client by John Grisham and how he takes the readers into Mark Sway’s traumatic experience and how he helps the readers understand Mark Sway’s position through imagery found. This study adopts library research (Library Research) which contains an in-depth collection of material on one or several subjects (Young, 1983; p. 188). This study covers the inclusion of primary sources as well as secondary sources. There are 5 types of imagery found in The Client. They are Visual Imagery, Auditory Imagery, Internal Sensation Imagery, Olfactory Imagery and Tactile Imagery.